The Category Is “Pandemic Queer”: Reading, Connecting, and Reimagining Literacy with LGBTQ+ Youth in the Age of COVID-19 - martin, shea wesley; Miller, Henry “Cody” (Radical Teacher, 2022)
The COVID-19 pandemic, coupled with the ensuing lockdown and political turmoil, ruptured many young people’s experiences and well-being, particularly students who face additional marginalization due to systemic oppression. A national survey conducted by the Trevor Project (2021) found that nearly 70% of LGBTQ youth noted that their health was “poor” most or all of the time during the COVID-19 pandemic. Factors contributing to this deterioration include LGBTQ youth being isolated from the supportive communities formed at school, lacking access to social services provided by schools, and being quarantined with family members who were unsupportive (Cohen, 2021; Valencia, 2020). These fissures in support and resource structures curtailed potentially affirming and integral education, social, and emotional experiences, particularly for LGBTQ youth who thrived in traditional schooling settings. However, it is also important to note that even prior to the COVID-19 pandemic, many schools were not idealized institutions for LGBTQ youth. K-12 schools, situated in the broader socio-political landscape of the United States, are bastions of homo-, trans-, and queerphobia (Mayo, 2014). Still, many LGBTQ young people employed resilience and ingenuity to create affirming and loving social circles, which were thus interrupted by restrictions, trauma, and isolation during the pandemic. As LGBTQ educators we sought to co-create an online community that could reflect the brilliance and joy of LGBTQ youth during the 2020-2021 school year. Through both our own experiences and the research, we know that LGBTQ youth find ways to construct community through online avenues, even when said avenues are limited and flawed, such as Tumblr (Cavalcante, 2019; Haimson, et al., 2021; Wargo, 2017). Building on our experiences as secondary English language arts teachers, we constructed a national online book club dedicated to reading, analyzing, and celebrating LGBTQ young adult literature with LGBTQ youth. After a summer of planning, we launched the online book club that resulted in over 125 secondary students from across the United States (and some international students) joining us for a year to engage in readings of Abdi Nazemian’s Like a Love Story (2019), Dean Atta’s Black Flamingo (2019), Gabby Rivera’s Juliet Takes a Breath (2016), and Mark Oshiro’s Anger is a Gift (2018). This article details how we structured a community of readers who worked to analyze young adult literature through intersectional and anti-oppressive lenses (Blackburn & Smith, 2010; Durand, 2015; Herman-Wilmarth & Ryan, 2015), deepen their critical consciousness relating to contemporary LGBTQ socio-political topics (Kelly & Currie, 2020), and leveraged social media and online avenues to construct community that expanded the boundaries of school hallways (Lucero, 2017; Mayo, 2014). Collectively, we seek to illustrate how LGBTQ+ communities (and queer pedagogies) can flourish and develop outside the limitations of K-12 institutions.